PENDIDIKAN ISLAM DAN ADAT ISTIADAT MELAYU: HUBUNGAN, NILAI, DAN TRANSFORMASI DI ERA MODERN - Rahmad Mahadi; Siska Wulandari; Ismail Sukardi; Nyayu Soraya (STKIP Subang, 2026)
Islamic education has an important role in shaping the character, morality and spirituality of students through internalizing the values ​​of the Koran and Hadith. In Malay society, Islamic education develops in harmony with customs based on the principle of